Pharmacogenetic of voriconazole antifungal agent in pediatric patients. (19th June 2018) - Allegra, Sarah; Fatiguso, Giovanna; Francia, Silvia De; Pirro, Elisa; Carcieri, Chiara; Cusato, Jessica; Nicolò, Amedeo De; Avataneo, Valeria; Perri, Giovanni Di; D'Avolio, Antonio
Aim: We explored the role of SNPs within the SLCO1B3, SLCO1B1, SLC22A6, ABCB1, ABCG2, SLCO3A1, CYP2C19, ABCC2, SLC22A1, ABCB11 and NR1I2 genes on voriconazole pharmacokinetics.Patients & methods: 233 pediatric patients were enrolled. Drug plasma Ctrough was measured by a HPLC-MS method. Allelic discrimination was performed by qualitative real-time PCR.Results: SLCO1B3 rs4149117 c.334 GT/TT (p = 0.046), ABCG2 rs13120400 c.1194 + 928 CC (p = 0.029) and ABCC2 rs717620 c.-24 GA/AA (p = 0.025) genotype groups significantly influenced Ctrough . ethnicity (p = 0.042), sex (p = 0.033), SLCO1B3 rs4149117 c.334 GT/TT (p = 0.041) and ABCB1 rs1045642 c.3435 TT (p = 0.016) have been retained in linear regression model as voriconazole predictor factors.Conclusion: Understanding how some gene polymorphisms affect the voriconazole pharmacokinetic is essential to optimally dose this agent.